PENGARUH VARIASI KOMPOSISI EKSTRAKTAN TERHADAP KEMAMPUAN ADSORPSI KLORAMFENIKOL MENGGUNAKAN MOLECULARLY IMPRINTED POLYMER (MIP) - Eucharistia Oktavia Firda Listiadi; Maria Monica Sianita (Unesa Journal of Chemistry, 2021)
The aim of this study is optimazing the extractant composition of methanol:acetic acid was with variations of 90:10(v/v), 85:15(v/v), and 80:20(v/v) in the (Molecularly Imprinted Polymer- Chloramphenicol) MIP-CAP synthesis. MIP-CAP is obtained from (Non Imprinted Polymer)NIP through the template extraction process. The template was extracted using maceration method and analyzed using High Performance Liquid Chromatography (HPLC) to determine the extracted CAP. The best extractant composition variation was determined based on % extraction and adsorption capability. The characterization of the MIP-CAP polymer was carried out using Fourier Transform Infra Red (FTIR) to see the presence of the –NO2 group. In this study, the best composition of methanol:acetic acid extractant was 80:20 (v/v) (20% acetic acid) with extraction % gain of 89,5158% and adsorption capability of 4,0725 mg/g with the value of Imprinting Factor (IF) of 3.7369. The higher the addition of acetic acid, the higher the % extraction and adsorption capability. The FTIR characterization of MIP-CAP showed that there was no absorption of the –NO2 group. Key words: CAP, MIP-CAP, Composition of Extractant